MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SMP NEGERI 1 BUNTULIA - Nursyaida; Jenli Abbas, Moh (Jurnal Riset Guru Indonesia, 2023)
Facilities and infrastructure are one part of the management that exists in educational institutions, facilities and infrastructure have a very important role in an organization, institution or educational institution. the purpose of this research is to find out the obstacles, namely the not optimal implementation of the management of infrastructure facilities and the lack of inadequate learning media. In this study used qualitative methods with a descriptive approach. Based on the results of research and data analysis on the management of facilities and infrastructure in improving the quality of learning at SMP Negeri 1 Buntulia, the author can conclude that most of the planning, procurement, maintenance, inventory, and disposal processes have been carried out well. Management of facilities and infrastructure is very influential on the quality of learning at school in this case, namely learning planning is mostly well achieved, learning implementation is well achieved, and learning outcomes are mostly the achievement of student achievement in the fields of attitude, behavior, knowledge, and skills.